THE EFFECTIVENESS OF SUPERVISION OF MADRASAH HEADS ON THE PROFESSIONAL IMPROVEMENT OF EDUCATORS AT MTS. MUHAMMADIYAH LEMBANGBU'NE, TOMPOBULU DISTRICT, GOWA REGENCY - Nurul Mamhmudah, Luthfiah; Mania, Sitti; Syamsuddin, Syamsuddin (LP2M IAI Al-Khairat Pamekasan, 2025)
The study of principal supervision is important because supervision influences improving teacher professionalism. This study uses quantitative methods to analyze the supervision of madrasah heads at MTs. Muhammadiyah Lembangbu'ne Kecematan Tompobulu Kabupaten gowa. The Population and sample are 14 educators. The sample technique used was saturated sampling. Data collected through instruments in the form of questionnaires or questionnaires, and documentation. Data analysis using descriptive statistical analysis and inferential statistical analysis. The results of this study indicate that the effectiveness of madrasah head supervision on the professional improvement of educators at MTs. Muhammadiyah Lembangbu'ne, Tompobulu District, Gowa Regency, obtained 1) The average value on the first variable, namely X (Effectiveness of madrasah head supervision), was 4.37 as a pre-test. 2) The second variable, namely variable Y (Professional educators of MTs. Muhammadiyah Lembangbu'ne), shows the average value of the post-test of 4.71. 3) Based on the results of statistical analysis related to the effectiveness of madrasah head supervision on improving the professionalism of educators at MTs. Muhammadiyah Lembangbu'ne Tompobulu District, Gowa Regency, is described in the effectiveness test, where before the supervision was held, the average professional value obtained was 4.37, and after the supervision, the average professional value obtained was 4.41. So it can be concluded that the hypothesis is accepted, so that it can be concluded that there is an influence between the variable (X), the effectiveness of madrasah head supervision, on the variable (Y), Professional Educators at MTs. Muhammadiyah Lembangbu'ne.